2020
DOI: 10.1159/000506619
|View full text |Cite
|
Sign up to set email alerts
|

Association of Copeptin, a Surrogate Marker of Arginine Vasopressin, with Decreased Kidney Function in Sugarcane Workers in Guatemala

Abstract: Background: Vasopressin is elevated in response to heat and dehydration and has been postulated to have a role in the chronic kidney disease of unknown origin being observed in Central America. The aims of this study were to examine whether the vasopressin pathway, as measured by copeptin, is associated with the presence of kidney dysfunction, and to examine whether higher fluid intake is associated with lower circulating copeptin and thereby preserves kidney health among sugarcane workers exposed to hot condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…In humans, copeptin (the stable vasopressin analogue) concentrations in plasma have been found to be significantly associated with increased risk of type two diabetes, chronic kidney disease, and cardiovascular disease [ 66 , 67 , 68 , 69 ]. Moreover, low water intake, which induces chronic vasopressin secretion [ 70 ], predicts the development of risk factors for coronary artery disease, for example, hyperglycemia [ 71 ].…”
Section: Metabolic Cardiovascular and Renal Effects Resulting From Po...mentioning
confidence: 99%
“…In humans, copeptin (the stable vasopressin analogue) concentrations in plasma have been found to be significantly associated with increased risk of type two diabetes, chronic kidney disease, and cardiovascular disease [ 66 , 67 , 68 , 69 ]. Moreover, low water intake, which induces chronic vasopressin secretion [ 70 ], predicts the development of risk factors for coronary artery disease, for example, hyperglycemia [ 71 ].…”
Section: Metabolic Cardiovascular and Renal Effects Resulting From Po...mentioning
confidence: 99%
“…Butler-Dawson et al demonstrated that cross-shift incidence of acute kidney injury was associated with both dehydration and lower electrolyte supplementation [ 33 ]. In a related study, Sorensen et al observed serum hyperosmolarity was associated with these cross-shift declines in kidney function, Sorensen et al [ 34 ] an effect that may be regulated via a vasopressin-mediated pathway of renal injury [ 35 ]. Ideally, to show the long-term success of such interventions in preventing kidney disease, longitudinal screening data should be combined with well-implemented interventions and longitudinal follow up.…”
Section: Introductionmentioning
confidence: 99%
“…The development and analysis of kidney injury biomarkers have also been the subject of research in this cluster. [68,[84][85][86][87][88][89][90][91][92][93] Despite the accelerated development in heat-related kidney health research shown in this study, gaps still exist in the research "hotspot" topics noted in this study. Such gaps exist, particularly in developing countries in Africa, Asia, the Middle East, and South America, which are reflected in their low research contributions and collaboration rates.…”
Section: Discussionmentioning
confidence: 84%